The Effect of Application of Planned Budget and Supply Chain Management on the Implementation of Applied Studies - Takleef Lafta, Oday; Bayan Talib, Ali; Akadhim Ismael, Hayfa (ExcelingTech, 2019)
Budgeting and supply chain management is in principle the allocation of resources and requires selection and prioritization. In this research, the factors affecting the implementation of the activity-based costing method in the budgeting of the various governmental organizations, has been investigated. The current study is an applied research and this research is a cross-sectional and descriptive-analytic study that utilizes a questionnaire to collect information. The statistical population of the study consisted of governmental organizations that had some kind of state budget in 2016. The results of the research indicate that in 60 governmental organizations, other than the ability to evaluate performance, other requirements are not required to implement the activity-based costing method in the operational budgeting, including employee empowerment, technical feasibility, legitimacy (legal, procedural and organizational legitimacy), and acceptability (political acceptability, management, and consistency of incentives). Based on the findings of the present study, in the governmental organizations studied, the effective factors necessary for performance-based costing in operational budgeting are not yet available. However, without using the new methods of costing in the operational budgeting, talking about reforms in the budgeting system, and shifting from program to operational budget is a difficult task.